Environmental enrichment selectively increases glutamatergic responses in layer II/III of the auditory cortex of the rat - Nichols, Justin (2007)
Prolonged exposure to environmental enrichment (EE) induces behavioral adaptation accompanied by detectable morphological and physiological changes. Auditory EE is associated with an increased auditory evoked potential (AEP) and increased auditory gating in the primary auditory cortex. We sought physiological correlates to such changes by comparing synaptic currents in control vs. EE-raised rats, in a primary auditory cortex (AI) slice preparation. Pharmacologically isolated glutamatergic or γ-amino-butyric acid-A (GABA(A)-) receptor-mediated currents were measured using perforated patch whole-cell recordings. Glutamatergic alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-receptor- (AMPAR-) mediated postsynaptic currents (EPSCs) displayed a large amplitude increase (64.2 ± 11.6 % in EE vs. control) accompanied by a rise-time decrease (−29.24 ± 5.7 % in EE vs. control) and decrease in pair pulse ratio in layer II/III but not in layer V. Changes in glutamatergic signaling were not associated with changes in the ratio between N-methyl-D aspartate-receptor-(NMDAR-) mediated vs. AMPAR- mediated components, in amplitude or pair pulse ratio of GABAergic transmission, or in passive neuronal properties. A realistic computational model was used for integrating in vivo and in vitro results, and for determining how EE synapses correct for phase error of the inputs. We found that EE not only increases the mean firing frequency of the responses, but also improves the robustness of auditory processing by decreasing the dependence of the output firing on the phase difference of the input signals. We conclude that behavioral and electrophysiological differences detected in vivo in rats exposed to an auditory EE are accompanied and possibly caused by selective changes in cortical excitatory transmission. Our data suggest that auditory EE selectively enhances excitatory glutamatergic synaptic transmission in layer II/III without greatly altering inhibitory GABAergic transmission.